Kebijakan Hukum Pidana Penerapan Pidana Kerja Sosial Untuk Mengurangi Overkapasitas Lembaga Pemasyarakatan Di Indonesia - Romi Saputra (Hang Tuah Law Journal, 2021)
Law is one element that cannot be separated in society, the relationship between law and society is a reciprocal relationship. The law will continue to develop along with the development of society, so that if in the course of time the community will develop, it will automatically require legal reforms that are able to keep pace with the development of society.The imposition of a crime against someone who commits a criminal act is a very important part in realizing a good criminal justice system, in this case the judge should be able to choose which type of crime is right for the perpetrator. The alternative to imprisonment, in this case social work punishment, gives the fact that imprisonment is increasingly being criticized for humanitarian considerations, philosophical considerations, and economic considerations. The criticisms of the negative consequences of imprisonment have given rise to the idea of looking for alternatives other than imprisonment even though imprisonment can be justified in terms of crime prevention, public safety, but imprisonment also has a fairly large negative assessment. Social work crimes for perpetrators of minor crimes can fulfill the elements of development and provide protection to the community. Elements of coaching that are oriented to individual criminals who are convicted of social work criminals are protected from negative impacts such as being labeled as criminals by the community, losing self-confidence so that the convict has self-confidence which is very necessary in the process of community integration.